Variable Attention Stimulus Trait (VAST) Spectrum Traits: A Brief Discussion on Attentional Control & Emotional Regulation in Attention Deficit-Hyperactivity Disorder (ADHD) - Hui, Xie Guo; Chua, Arnold Chee Keong; Singh, Harjit (Asian Journal of Interdisciplinary Research, 2023)
Attention Deficit-Hyperactivity Disorder (ADHD) was first identified in 1902 by a British pediatrician, Sir George Still, as an abnormal defect in children’s moral control that caused poor control of their behavior despite their average and/or above intellectual capacity. It was not until the late 20th century when the American Psychiatric Association formally recognized ADHD as a mental disorder, whose hallmarks are excessive amounts of inattention, hyperactivity, and impulsivity. Also known as the triad of impairments in ADHD, these symptoms are pervasive, impairing in multiple contexts, and otherwise age-inappropriate. Only recently, Hallowell and Ratey (2021) introduced the concept of Variable Attention Stimulus Trait (VAST) in their book ADHD 2.0 to describe the condition. They argued that VAST/ADHD is unrelated to intelligence and has nothing to do with the deficit of attention. VAST/ADHD describes about how each brain/mind is uniquely wired affecting the way one deals with stimulation and attention. In this paper, the authors have chosen to explore two of the traits on the VAST/ADHD spectrum - (i) attentional control/sustained attention, and (ii) emotional regulation/impulse control - to illustrate the condition of ADHD as a variability of attention rather than a deficit of attention.